A Correlative Study Between Personality Traits and the Preference of Site Selection in Cosmetic Treatment - Qian, Huan; Ling, Yuxiao; Wang, Chen; Lenahan, Cameron; Zhang, Mengwen; Zheng, Min; Shao, Anwen (Frontiers in Psychiatry, 2021)
Background: Cosmetic treatment was closely associated with beauty seekers' psychological well-being. Patients who seek cosmetic surgery often show anxiety. Nevertheless, not much is known regarding how personality traits relate to the selection of body parts that receive cosmetic treatment. Aims: This study aims to investigate the correlation between personality traits and various selection sites for cosmetic treatment via Eysenck Personality Questionnaire (EPQ). Methods: A cross-sectional approach was adopted to randomly recruited patients from a general hospital planning to undergo cosmetic treatments. All respondents completed the EPQ and provided their demographic information. The EPQ involves four scales: the extraversion (E), neuroticism (N), psychoticism (P), and lying scales (L). Psychological scales were evaluated to verify that people who selected different body sites for cosmetic intervention possessed different personality portraits. Results: A total of 426 patients with an average age of 32.14 ± 8.06 were enrolled. Among them, 384 were females, accounting for more than 90% of patients. Five treatment sites were analyzed, including the body, eye, face contour, nose, and skin. Comparatively, patients with neuroticism were more likely to undergo and demand rhinoplasty (OR 1.15, 95% CI 1.07–1.24, P < 0.001). Face contour treatment was commonly associated with extraversion (OR 1.05, 95% CI 1.00–1.11, P = 0.044), psychoticism (OR 1.13, CI 1.03–1.25, P = 0.013), and neuroticism (OR 1.05, CI 1.01–1.10, P = 0.019). Conclusions: This novel study attempted to determine the personality profiles of beauty seekers. The corresponding assessments may provide references for clinical treatment options and enhance postoperative satisfaction for both practitioners and patients.